2020
DOI: 10.1515/jpem-2020-0079
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-induced rickets-osteomalacia: an enigma

Abstract: ObjectiveWe report a case of pediatric thoracic tumor-induced osteomalacia (TIO) causing severe hypophosphatemic rickets with delayed diagnosis and emphasize on timely management of this rare entity.Case presentationA young boy presented with rickets since five years of age. Biochemical evaluation revealed hypophosphatemia, hyperphosphaturia, elevated alkaline phosphatase and normal calcium levels. Initially managed as hereditary hypophosphatemic rickets, he was given phosphorus supplements and calcitriol. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The clinical and biochemical manifestations of TIR/O in children and adolescent patients most commonly reported in previous studies (3,(5)(6)(7)(8)(9)(10)(11)(12) are similar to the ones observed in our patients. However, some patients initially presented at a much younger age (9 months 5 years), (6,11,13) had an uncommon tumor location (intracranial lesion), (7) or had an atypical histopathology (central giant cell lesion).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The clinical and biochemical manifestations of TIR/O in children and adolescent patients most commonly reported in previous studies (3,(5)(6)(7)(8)(9)(10)(11)(12) are similar to the ones observed in our patients. However, some patients initially presented at a much younger age (9 months 5 years), (6,11,13) had an uncommon tumor location (intracranial lesion), (7) or had an atypical histopathology (central giant cell lesion).…”
Section: Discussionsupporting
confidence: 91%
“…TIR/O cases in children and adolescents are scarcely reported in the literature, either as case reports (5)(6)(7)(8)(9)(10)(11)(12)(13) or in reviews. (3,9) Our study comprehensively analyzed the clinical, biochemical, radiological, and pathologic findings associated with this rare entity in a large retrospective cohort of Chinese children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The multifocality of these tumors makes it prudent to look for additional lesions on whole-body imaging in these cases, especially in cases that do not show improvement after resection. Although less commonly described, TIO should be kept in the differentials for children presenting with refractory hypophosphatemic rickets (34).…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric cases have been infrequently reported. 4 The median age at the time of diagnosis is 44-48 years of age. 5,6 Tumor locality is unpredictable; PMTs can be found in any osseous or soft-tissue location and uncommonly involve the skin.…”
Section: Discussionmentioning
confidence: 99%